E-Learning and MOOC: The Cross Currents in Education and the Benefits for Learners: Exploring the Impact of E-Learning and MOOC on Modern Education (Journal of Advances and Scholarly Researches in Allied Education, 2017)
With the increased use of internet, there is a growing awareness of the need to become more digitally literate. With Web 2.0, software has become more open source, providing users with a greater ability to influence the web. Internet based learning practices affect the way learners acquire knowledge. The learning practices in various disciplines have changed in a large measure. The arts and humanities, science disciplines, and engineering and technology, have gone through innovating teaching and learning methodologies. MOOC is bringing a grass root level change in educational practices. Individuals and institutions offer courses using platforms like Udemy, Udacity, Coursera, EdX etc. Moreover handheld devices like tablet computers and smartphones make learning more effective and personal. In Mobile learning using mobile applications and the Internet of Things rely the future of modern educational practices.